Examining the Influence of Mild Traumatic Brain Injury and Posttraumatic Stress Disorder on Alcohol Use Disorder in OEF/OIF Veterans. Issue 1 (1st January 2015) - Miles, Shannon R.; Graham, David P.; Teng, Ellen J.
ABSTRACT: Objectives: Examine (1) impact of mild traumatic brain injury (mTBI) on posttraumatic stress disorder (PTSD) symptoms, (2) frequency of alcohol use disorder in male and female combat Veterans, and (3) influence of PTSD and mTBI on alcohol use disorder. Method: A retrospective medical-record review extracted the following data for Operation Enduring Freedom/Operation Iraqi Freedom Veterans ( N = 1, 278) who completed a semi-structured mental health evaluation: alcohol use disorder diagnoses, PTSD symptom criteria, and Brief Traumatic Brain Injury Screen. Logistic regressions tested if PTSD and mTBI predicted which Veterans had an alcohol use disorder diagnosis. Results: Veterans with mTBI had more re-experiencing, avoidance, and hyperarousal symptoms than Veterans without mTBI. Men and women differed regarding alcohol use. For men, PTSD predicted alcohol use diagnosis while mTBI did not. For women, neither mTBI nor PTSD predicted alcohol use diagnosis. Conclusion: Findings from this study can inform treatment providers by alerting them to the possibility of subthreshold PTSD in Veterans with mTBI. Providers may begin PTSD treatments or consider targeting hyperarousal symptoms early in treatment to reduce distress. PTSD is also uniquely associated with alcohol use disorder in male Veterans, while more research on predictors of alcohol use disorder is needed for female Veterans.